Single-stage single-phase grid connected inverter proportional resonant and maximum power point tracking controllers for enhanced photovoltaic system performance - Kabba, Abdelaziz; Lassioui, Abdellah; El Fadil, Hassan (International Journal of Electrical and Computer Engineering (IJECE), 2026)
The paper develops a current control methodology for a single-phase grid-tied DC/AC inverter applied to photovoltaic (PV) energy conversion systems. It incorporates an algorithm for finding the optimal voltage and current points to obtain maximum power point tracking (MPPT), the purpose of which is to ensure better energy extraction. This is followed by a proportional-integral (PI) controller to generate the reference current. In addition, a proportional-resonant (PR) controller is used to infinitely amplify the fundamental frequency signal, which makes it possible to eliminate the steady-state error. The analytical foundations of the PR controller are presented and substantiated through simulation studies implemented in MATLAB/Simulink. The phase-locked loop (PLL) is used for synchronization, enabling accurate phase detection of the grid voltage for effective power injection. An LCL filter is also implemented between the inverter and the grid. The results provided by the dedicated software confirm the effectiveness of the proposed control system.